2009
DOI: 10.2310/jim.0b013e3181946fec
|View full text |Cite
|
Sign up to set email alerts
|

Medical Student Research Exposure via a Series of Modular Research Programs

Abstract: Although structured programs can provide step-wise research experiences of increasing intensity, students may not experience a training pipeline in which each stage relies on those before and after, and instead may sample an a la carte selection of research-based enrichment opportunities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 17 publications
1
26
0
3
Order By: Relevance
“…The data extraction and quality assessment worksheet and the relevant sensitivity plots can also be found in the supporting information files ( S3 and S4 Files , respectively) [7,8,10,11,2390]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The data extraction and quality assessment worksheet and the relevant sensitivity plots can also be found in the supporting information files ( S3 and S4 Files , respectively) [7,8,10,11,2390]. …”
Section: Resultsmentioning
confidence: 99%
“…Both of these outcomes are explorative in nature (rely on proportions rather than odds ratios) and have been quantitatively pooled to yield a weighed estimate value. The results have been summarized in Fig 3 [7,10,26,28,32,4749,52,54,55,58,63,6769,71–75,8082,85,9092] . …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These courses aim to offer students' opportunities to acquire basic skills of research through theoretical and practical sessions. Generally, the common barriers to undergraduate medical research programs include lack of (1) logistics and infrastructure support, (2) defined set of skills to be developed through research processes, (3) protected time in the curriculum, (4) project selection so that students can provide meaningful contributions, and (5) feedback so that the research process becomes a learning experience (Nathan 1998;Moskowitz & Thompson 2001;Langhammer et al 2009). In contrast, the URC at Alfaisal University College of Medicine developed a central body which was able to overcome most of the aforementioned barriers by identifying and securing research positions at internationally and locally reputed laboratories.…”
Section: Resultsmentioning
confidence: 99%
“…Preclinical students tend to focus on basic science research 23 while clinical students are generally more interested in clinical research. 24 It has been reported that senior medical students can be productive even during research electives as short as 4 weeks. 25 Regardless of the amount of time spent, early exposure can help the student realize if they are suitable for research.…”
Section: Attitudes Toward Researchmentioning
confidence: 99%